PICTURE AND ATTITUDE TOWARDS SELF-MEDICATIONS OF ANTIBIOTIC USE IN THE COMMUNITY IN DOPALAK VILLAGE (Journal of Health, Technology and Science (JHTS), 2025)
This study has a general objective to determine the level of knowledge and attitude of antibiotic use through self-medication (self-treatment) in residents of Dopalak Village, Paleleh District, Buol Regency. The method in this study uses a quantitative approach based on positivity (concrete data) with analytical observation with a descriptive research design. The study was conducted by collecting data using a questionnaire on the level of knowledge and attitudes. Based on the results of the study, a description of the level of knowledge of the Dopalak Village community regarding antibiotic self-medication was obtained, namely with the category of less being the most, namely 24 people (55.81%) and enough as many as 17 people (39.54%), while in the attitude category, residents of Dopalak Village in the use of antibiotics found that as many as 26 people (60